PENGARUH ASPEK KEUANGAN DAN KOMPETENSI SUMBER DAYA MANUSIA (SDM) TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KELURAHAN PALEBON KECAMATAN PEDURUNGAN SEMARANG - Handoyono, Rudi; Farizi, Musyafa Al; A, Lilis Mardiana; H, Retno Winarti (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This research was conducted in Micro, Small and Medium Enterprises (MSMEs) in Palebon Village from April to October 2024. The subjects in this study were directly MSME owners in Palebon Village. This research is a comparative causal research, which is a type of research with problem characteristics in the form of a cause-and-effect relationship between two or more variables. The population in this study is all MSME actors in Palebon Village. The number of MSMEs in Palebon Village is 43. Based on the results of this study, it shows that Finance has no influence on the performance of MSMEs in the Pleburan Village. This can be seen from the t calculation obtained of 1.284 < t table of 2.021 and significance (p value) of 0.207 > 0.05. Based on the results of this study, it shows that HR Competence has a significant influence on the Performance of MSMEs in the Pleburan Village. This can be seen from the t calculation obtained of 2.677 > t table of 2.021 and significance (p value) of 0.011 < 0.05. Based on the above, it can be seen that the F value is calculated as 5.513 > 3.23 F table with a significance of 0.008. The significance value is < 0.05 so this result identifies that the regression model is feasible to use to predict dependent variables. The independent variables in this study, Finance and Human Resources Competencies simultaneously have an influence on the Performance of MSMEs in the Pleburan Village